Personality traits: an important factor affecting fear of movement in dialysis patients - Zhang, You; Zhang, Ruike; Miao, Xiaoyong; Li, Maoting; Zhang, Lingyan; Li, Lu; Liu, Yuting; Shao, Qing; Ding, Lingling; Su, Tong; Guo, Zhiyong; Liu, Nanmei (Frontiers in Psychiatry, 2025)
BackgroundThis study investigated predictive factors and personality determinants of kinesiophobia (fear of movement) in dialysis patients. Methods: Using the Chinese versions of the Ten-Item Personality Inventory (TIPI-C) and Tampa Scale for Kinesiophobia Heart (TSK-SV heart), we assessed 329 patients from December 2022 to February 2023. The influencing factors of fear of movement were identified by univariate analysis and multiple linear regression.ResultsThe mean score of fear of movement for dialysis patients was 45.128 (45.128 ± 7.023). Multiple linear regression revealed that advanced age,local medical insurance, and lower education significantly predicted higher kinesiophobia scores, while exercise habits, being married, alcohol and tobacco use served as protective factors. Personality analysis demonstrated that lower extraversion, emotional stability, and conscientiousness were associated with greater kinesiophobia.ConclusionsPersonality determinants were significantly associated with fear of movement. These findings emphasize the clinical utility of personality assessment in identifying high-risk patients and personalizing rehabilitation strategies for this vulnerable population.